PREDICTORS OF SMOKING PRACTICE AMONG HIGH SCHOOL LEARNERS - Mokonoto, Dimakatso; Naidoo, Shan (Journal of Community and Health Sciences, 2020)
Introduction: Smoking presents a challenge to the future health status of learners who are smokers. There are over one billion smokers in the world today. Smoking is evident among the youth of South Africa with 19.6% of them being involved in this habit. Objectives: The objective of this study was to investigate the prevalence of smoking in grade twelve learners. It was further investigated whether socio-demographic factors may influence the prediction of the smoking practice among these learners. Methods: This paper is reporting on a selective concept of a larger cross-sectional descriptive survey. Participants: All learners who gave informed consent and who were enrolled during 2001 as grade twelve learners at three selected schools (n=452), were recruited to participate in the survey. Setting: The study was done in the multi-cultured community of Tshwane South Education District located in Gauteng Province. The district was divided into three strata. One school was selected randomly from each stratum. Intervention: A self-administered questionnaire. Results: There were 401 (89%) returned questionnaires. Overall 104 (26%) of students were current smokers. Smoking practice was a significantly associated with race, gender, smoking habits of parents, siblings and friends and fathers' employment status. Conclusion: Smoking amongst grade 12 scholars is on the increase and specific predictors may play a role to influence the uptake of smoking among learners.